Politik Identitas Dalam Panggung Pilwana (Studi Kasus Pemilihan Wali Nagari Sungai Jambu Kecamatan Pariangan Kabupaten Tanah Datar) - Metri Hertika; Novi Budiman (UIN Mahmud Yunus Batusangkar, 2022)
This study aims to explaint that identity politics can color the election wali nagari (pilwana) in the guava river in 2021. And this study tries to discuss te main problems of the form of identity politics played by candidate candidates or political elites as a means of gaining power in occupying a position. Therefore, this study shows the identity of ethnic symbols, regions (jorong) through the use of networks of community leaders and supporters who come rom the reginÔÇÖs own sons in the pilwana.Ormas┬á Islam┬á Bermuatan Politik Yang Terlarang┬á Di Indonesia